2016
DOI: 10.1111/dom.12716
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cell adaptation in pregnancy

Abstract: Pregnancy in placental mammals places unique demands on the insulin-producing β-cells in the pancreatic islets of Langerhans. The pancreas anticipates the increase in insulin resistance that occurs late in pregnancy by increasing β-cell numbers and function earlier in pregnancy. In rodents, this β-cell expansion depends on secreted placental lactogens that signal through to the prolactin receptor. Then at the end of pregnancy, the β-cell population contracts back to its pre-pregnancy size. In the current revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
155
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 91 publications
4
155
0
5
Order By: Relevance
“…The compensatory changes in human BCM remain controversial as the dynamics of BCM expansion are hypothesized to be slightly different from those in mouse (Baeyens et al . ). Nonetheless, the only two human studies conducted to date have both reported an increase in β‐cell area in pancreata of pregnant women at postmortem (Van Assche et al .…”
Section: Introductionmentioning
confidence: 99%
“…The compensatory changes in human BCM remain controversial as the dynamics of BCM expansion are hypothesized to be slightly different from those in mouse (Baeyens et al . ). Nonetheless, the only two human studies conducted to date have both reported an increase in β‐cell area in pancreata of pregnant women at postmortem (Van Assche et al .…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive success depends on an intensive and rich dialogue among mother, placenta, and fetus. The adaptations required for pregnancy appear to involve virtually all maternal organs/systems, including the metabolic/ endocrine (1)(2)(3)(4)(5)(6), cardiovascular (7)(8)(9)(10)(11)(12), respiratory (13), gastrointestinal (12,(14)(15)(16)(17)(18)(19)(20)(21), hematologic (22,23), and central nervous systems (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the physiology of pregnancy has spanned decades, and has largely depended upon available technological capabilities to study parameters that change with gestational age. Such parameters have been studied with relatively simple methods, such as hormonal determinations (20,21,27), concentrations of nutrients/fuels (glucose (17)(18)(19), lipids(28-33), proteins(34-40), amino acids(41-43)), blood pressure (8,44), cardiovascular function (9,11), spirometry (13,16), immunological assays (14,24,45), and different tests of central nervous system function (25,26). These studies have been essential to understand changes in body composition (4,18), physiologic adaptation (10,13), pathophysiology of selected pregnancy complications (17,(46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%
“…For normal glucose tolerance to be maintained in the setting of the insulin resistance of late gestation, the b-cells must markedly increase their secretion of insulin. It is believed that this enhanced secretion is achieved through the expansion of b-cell mass in response to circulating factors, including prolactin and placental lactogens (1,2). Conversely, failure of this compensatory response will result in maternal hyperglycemia or gestational diabetes mellitus (GDM) (3).…”
mentioning
confidence: 99%